Pelatihan Pembuatan Spesimen Awetan Tumbuhan Dan Hewan Sebagai Media Pembelajaran Dalam Mengungkap Keanekaragaman Hayati - Yulianty; M Kanedi; Kusuma Handayani; Achmad Arifiyanto (CV. Multi Kreasi Media, 2023)
Learning media is one of the methods used in the learning process and is highly needed in facilitating material delivery. In presenting biology materials, such as biodiversity, attractive media is crucial in helping students understand without excessive memorization. Preserved specimen is an example of learning media in this situation. Wet and dry herbariums are one of the preserved specimens commonly used by teachers. Meanwhile, bioplastic creation using resin has not been a common practice. Some advantages of bioplastic creation include more beautiful and durable results while also can be created as keychains. The aim of this community service is to train teachers in SMA 15 Bandar Lampung in making animal and plant preserved specimens through various procedures. After the training, there was an increase in knowledge and skill in making preserved specimens. The average pre-test score was 56.25, while the average post-test was 90,63. The average score escalated by 34,38 points.